(3GdeHGOF (B-(3GdfXQjGJ(B-(3hGdhXGFas - (3ehab MOjO(B, (3eMeO s ((3YeGf(B:s (3OGQ GdMGeO ddfTQ h GdJhRjY(B,s, 2001)
(3eaghe GdefXeI GdGOGQjI h fTGWGJ GdeOjQ h GdegGQGJ GdGOGQjI h fXQjGJ GdGOGQI h GdJWhQ GdJGQjNj ddGOGQI h GdHjFI GdGOGQjI ceG Je JfGhd CfhGY h NWhGJ h COhGJ GdJNWjW h cPG GdJfXje HGdJWQb Gdi JUeje Gdgjcd GdJfXjej h GdJbSjeGJ GdGOGQjI h cPG GdbjGOI h GdOGaYjI h fXe h GdecGaBJ h GdQbGHI h UfY GdbQGQ GdPj jYJHQ LhQ Yed GdeOjQ(B.s
(3eQGLY U(B.293s
Keywords: (3GdGOGQIs